Preoperative low muscle mass and malnutrition affect the clinical prognosis of locally advanced gastric cancer patients undergoing radical surgery - Zhao, Ailing; Hou, Chong; Li, Yingzi; Liu, Yipin (Frontiers in Oncology, 2023)
Background: Gastric cancer is a common and highly aggressive malignant tumor of the gastrointestinal tract that poses a serious threat to human life and health. With the advancement of medical technology, gastrectomy has become a safer surgical procedure, but it still has a high recurrence and mortality rate after surgery. The prognosis of gastric cancer patients after surgery is not only related to tumor-related factors (i.e., tumor stage) but the patient's nutritional status. This study aimed to investigate the effect of preoperative sarcopenia combined with the prognostic nutritional index (PNI) on clinical prognosis in advanced gastric carcinoma. Methods: The clinical data of 136 patients with advanced gastric carcinoma diagnosed by pathology and undergoing radical gastrectomy were retrospectively reviewed. To analyze the influencing factors of preoperative sarcopenia and its correlation with prognostic nutritional index. The relationship between PNIS and clinicopathological characteristics was analyzed. Univariate and multivariate analyses were performed to identify risk factors for overall survival (OS). Patients with both sarcopenia and low PNI (≤46.55) were assigned a score of 2, and those with only one or neither of these abnormalities were assigned a score of 1 or 0, respectively, according to the new prognostic score (PNIS). Results: Sarcopenia was associated with a lower PNI (P < 0.01). The optimal cut-off value of PNI was 46.55, the sensitivity was 48%, and the specificity was 97.1%. There were 53 (38.97%), 59 (43.38%), and 24 patients (17.65%) in the PNIS 0, 1, and 2 groups, respectively. A higher PNIS and advanced age were independent risk factors for postoperative complications (P < 0.01). The overall survival rate in patients with PNIS 2 score was significantly poorer than in patients with scores of 1 or 0 (3-year OS: 45.8% vs 67.8% vs 92.4%, P < 0.001). A Multivariate Cox hazards analysis showed that PNIS 2, depth of tumor invasion, vascular invasion, and postoperative complications were independent predictors of the poor 3-year survival in patients with advanced gastric cancer. Conclusions: The combination of sarcopenia and the PNI score system can be used to predict the survival outcome of patients with advanced gastric cancer.